The classification and mechanisms of coal-gas compound dynamic disasters: a preliminary discussion. (2019) - Wang, Kai; Du, Feng
With the development of deep mining in recent years, there appears a new form of dynamic disaster, which is known as coal-gas outburst and rockburst compound dynamic disaster. It is also called as coal-gas compound dynamic disaster for academia. In this paper, we propose a new classification system of coal-gas compound dynamic disasters. The coal-gas compound dynamic disasters are divided into three types named rockburst-induced outburst dynamic disaster, outburst-induced rockburst dynamic disaster, outburst and rockburst coupling dynamic disaster. And the occurrence mechanism and energy criterion of each kind of compound dynamic disaster are discussed. We suggest that integrated prevention and control strategies of coal-gas compound dynamic disasters should be adopted by eliminating the gas internal energy and releasing the elastic energy. We also believe that using big data to improve the prediction and control level of coal-gas compound dynamic disasters is the key research direction in the future.